Analisis Dampak Sosial Pendidikan Tayangan Infotainment TV Swasta di Indonesia - HASMIRA, MIRA HASTI (TINGKAP, 2012)
Mass media should ideally function as information, education and entertainment channels. However, in Indonesia, the mass media perform its function more as entertainment through many channels such as infotainment shows that more charged in Indonesian celebrity gossip. This often raises a lot of Indonesian social problems in society as one of the unplanned effects by the media. As part of the social sciences, science of communication should be able to provide insight to the media as communicators to be more intelligent to educate the people of Indonesia so many social problems that arise as a result of unplanned effects by the media could at least be minimized. Kata Kunci : infotainment, information, mass media